Exploring Anti-racism Within the Context of Human Resource Management in the Health Sector in Aotearoa - Heke, D; Came, H; Birk, M; Gambrell, K (Queensland University of Technology, 2022)
Compelling evidence continues to demonstrate that racism is a modifiable determinant of health inequities. Despite growing recognition of this it is less clear how from a human resource perspective to engage in effective anti-racism. Through a review of human resource and anti-racism literature, the white, Indigenous and racialised authors examined existing approaches to anti-racism applicable to the health system in Aotearoa. Two systemic organisational approaches were identified: diversity training and dismantling institutional racism. Recruitment processes, talent management and retention were human resource specific sites for interventions. Insights from anti-racism scholarship including upholding te Tiriti o Waitangi and engaging in decolonising to enable transformative change. Power-sharing remains at the heart of anti-racism praxis. A health sector response needs to be co-created with Māori and those with the political will to enable transformation. Given racism has a geographic specificity, solutions need to be informed by the cultural, political, social, and historical context.
Keywords: Anti-racism praxis; Human resource development; Indigenous; health; Te Tiriti o Waitangi; Decolonisation